The double-edged sword of self-tracking: investigating factors of technostress in performance-oriented cycling and triathlon - Werner, Mirjam; Bischof, Andreas (Frontiers in Sports and Active Living, 2024)
This study is dedicated to the investigation of technostress caused by self-tracking in performanceoriented amateur sports and thus addresses a significant research gap in the understanding of stress factors operating in this specific context. Although technostress in occupational and private settings has been extensively researched, there is a lack of knowledge about the effects and specifics of technostress caused by the use of self-tracking technologies in sportssuch as wearables and performance monitoring apps in sports. A total of 16 stress factors were identified, eight of whichinformation overload, distraction, unavailability, loss of control, lack of sense of achievement, unreliability, complexity and self-monitoring -are already known from the professional context and were transferred to the sports context. In addition, eight new stress factors specific to performanceoriented amateur sport were identified: Performance enhancement imperative, lack of context, digital visibility, feedback incorporation, measurement data fixation, comparison pressure, permanent monitoring and perception discrepancy. The study is based on a qualitative research approach with guided interviews conducted with performance-oriented amateur triathletes. The findings of this study contribute to a deeper understanding of the dynamic and contextual nature of technostress in sport and provide a basis for the development of targeted intervention strategies aimed to reducing minimize technostress, in this specific group of athletes such as adaptive training programs or personalized feedback systems. The results thus provide a valuable starting point for future research, particularly for the investigation of coping strategies in relation to the identified stress factors. In addition to identifying eight new sport-specific technostress factors, this study clearly delineates how traditional work-related technostress factors are applicable to amateur sports. This contextual adaptation helps in understanding the unique pressures faced by amateur athletes and distinguishes this study within the field.